Methods of teaching programming - Szlávi, Péter; Zsakó, László (Teaching Mathematics and Computer Science, 2003)
Programming methodology is one of the oldest fields of IS education, and thus various methods have evolved for its teaching. While some of them could be used effectively in primary or secondary education, others are more suited for students in higher education. The methods themselves determine the structure and curricula of courses such as Programming methodology, Data types and algorithms, Programming technology.